2006
DOI: 10.1007/s10562-006-0208-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of lanthanum carbonate phases of Ni/La0.98Sr0.02O x catalyst over the oxidative transformation of methane

Abstract: This work combines the advantages of $2 mol.% Sr/La 2 O 3 (i.e. La 0.98 Sr 0.02 O x ) for OCM (oxidative coupling of methane) with welldispersed nickel over metal oxides for POM (partial oxidation of methane) to efficiently transform methane to desirable products. The catalysts were prepared by sequential impregnation and characterized by X-ray diffraction, thermogravimetric analysis, scanning electron microscopy, temperature-programmed reduction, temperature-programmed decomposition of carbonates and BET surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…(4)) would increase with the time of exposition to air. 23 Fig. 3(a and b), an experimental weight loss ( M/M 0 ) of about 13.5 wt.% occurred during heating, which proceeded in three steps.…”
Section: Thermal Behaviour Of La 2 O 3 /Sio 2 Mixturementioning
confidence: 97%
“…(4)) would increase with the time of exposition to air. 23 Fig. 3(a and b), an experimental weight loss ( M/M 0 ) of about 13.5 wt.% occurred during heating, which proceeded in three steps.…”
Section: Thermal Behaviour Of La 2 O 3 /Sio 2 Mixturementioning
confidence: 97%
“…These species are present on the perovskite surface. Rudolfo et al also reported a peak of reduction at 573 K, which is attributed to NiO on the surface [33]. The second step is observed at ~ 500 °C, due to the reduction of Ni 3+ in the perovskite to Ni 2+ which generates the formation of the La2Ni2O5 phase, this last being reduced at ~ 630 °C as indicates the third peak.…”
Section: Temperature-programmed Reduction (Tpr)mentioning
confidence: 90%
“…Figure 1 also shows the reduction of nickel oxide under four different peaks. The peak at 305°C can be attributed to the reduction of bulk NiO [22,23]. The peaks at 352°C [24].…”
Section: Temperature-programmed Reductionmentioning
confidence: 99%